Knowledge of pregnant women regarding the Family Planning Law and the insertion of a copper intrauterine device (IUD) in the immediate postpartum period (Research, Society and Development, 2026)
This study aimed to evaluate the level of knowledge of pregnant women attending a reference maternity hospital in Belém, Pará, regarding the Family Planning Law and the insertion of the copper intrauterine device (IUD) in the immediate postpartum period. A cross-sectional and descriptive study, with a quantitative-qualitative approach, was conducted with 116 pregnant women attending a reference hospital in the state for high-risk maternity care. Data collection was carried out using a structured questionnaire containing questions about sociodemographic characteristics and others related to knowledge about some aspects of Law No. 14.443/2022 and about the copper IUD. Statistical analysis was performed using Jamovi® software, considering a significance level of p ≤ 0.05. The results showed a low level of knowledge among pregnant women regarding both the Family Planning Law and the characteristics and advantages of the copper IUD in the immediate postpartum period, as well as significant associations between sociodemographic variables and the degree of information. These findings reinforce the importance of strengthening contraceptive counseling during prenatal care and obstetric care, as a strategy to promote reproductive autonomy and improve the quality of care.